THE INFLUENCE OF BACCALAUREATE AVERAGE SCORE ON ACADEMIC ACHIEVEMENT OF UNDERGRADUATES - Carmen Alina POPA; Laura BOCHIŞ (Studia Universitatis Babes-Bolyai, 2016)
The present study researched: 1.The correlation among the baccalaureate average grade for admission to the university and average grades earned each semester 2. The correlation among grades for each semester of the three year program. The data used in this study includes scores and grades for the 125 students who had taken their entrance exam in the 2012/2013 academic year. Data was analyzed using the Bravais-Pearson correlation coefficient and the Cohen criteria for analyzing effect size. The results indicate that there is a significant positive correlation between the entrance scores and the grades for the first five semesters. The data indicate that the correlation between the exam average and GPA average is not significant for the last semester. The effect size scores indicate that this significance is medium for the first two semesters (.48 and .43); the effect size is low for the next three semesters (.37, .22, .20). The results also indicate there are significant positive correlations between the GPA of each of the semesters. These results indicate that each semester's GPA average has a high effect size score for the subsequent semesters. The effect size scores are lower for each subsequent semester but remain in the high effect size levels, ranging from .82 to .72. The conclusion drawn from this data is that in order to develop more consistent decision-making predictions the university should use both baccalaureate averages and GPA both in the transition from high school to university and between semesters and years within the university program. ZUSAMMENFASSUNG. Die vorliegende Studie erforschte: 1. Die Korrelation zwischen dem Bakkalaureat Durchschnittsnote für die Zulassung zur Universität und die Durchschnittsnoten erwarb jedes Semester. 2. Die Korrelation zwischen den Noten für jedes Semester des Dreijahresprogramm. Die Daten verwendet in dieser Studie umfassen Noten und Wertungen für 125 Studenten, die ihre Aufnahmeprüfung im Studienjahr 2012/2013 übernommen haben. Die Daten wurden mit dem Bravais-Pearson-Korrelationskoeffizient und die Cohen Kriterien für die Effektgröße analysiert. Die Ergebnisse zeigen, dass es eine signifikante positive Korrelation zwischen den Eingangswertungen und die Noten für die ersten fünf Semester gibt. Die Daten zeigen, dass die Korrelation zwischen der Prüfung Durchschnitt und GPA Durchschnitt für das letzte Semester nicht signifikant ist. Die Effektgröße Werte zeigen, dass diese Bedeutung für die ersten beiden Semester Medium ist (0,48 und 0,43); die Effektgröße ist für die nächsten drei Semestern niedrig (0,37, 0,22, 0,20). Die Ergebnisse zeigen auch, dass es eine es signifikante positive Korrelation zwischen der GPA jedes Semester gibt. Diese Ergebnisse zeigen, dass GPA Durchschnitt jedes Semesters eine hohe Effektstärke- Wert für den nachfolgenden Semestern hat. Die Effektgröße Werte sind niedriger für jedes weitere Semester aber bleiben in den hohen Effektgröße Niveaus, von 0,82 bis 0,72. Die Schlussfolgerung anhand diesen Daten ist, dass, um einheitlichere Entscheidungsfindung Prognosen zu entwickeln, sollte die Universität sowohl Bakkalaureat Durchschnittswerte und GPA in den Übergang von Gymnasium zur Universität und zwischen Semester und innerhalb Jahren der Universität Programm verwenden. Schlüsselwörter: Pädagogik der Grund- und Vorschulbildung, Abitur-Prüfung Durchschnittsnote, Notendurchschnitt pro Semester, GPA, Zugangsvoraussetzungen, akademischen Erfolg